2020
DOI: 10.32322/jhsm.698380
|View full text |Cite
|
Sign up to set email alerts
|

The level of anxiety and depression in patients admitted to an infertility clinic

Abstract: The level of anxiety and depression in patients admitted to an infertility clinic Bir infertilite kliniğine başvuran hastalarda anksiyete ve depresyon düzeyleri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Consequently, Gürbüz et al [51] discussed that infertile couples without sufficient counseling from healthcare providers might have many biopsychosocial health problems during the IVF treatment procedure. Many studies, such as [52][53][54] confirm that women who do not receive health strategies have high levels of stress; this is in alignment with the result of the present study, which observed that most of the women before the health education program had a high level of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Gürbüz et al [51] discussed that infertile couples without sufficient counseling from healthcare providers might have many biopsychosocial health problems during the IVF treatment procedure. Many studies, such as [52][53][54] confirm that women who do not receive health strategies have high levels of stress; this is in alignment with the result of the present study, which observed that most of the women before the health education program had a high level of stress.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Furthermore, elevated stress levels have been associated with reduced embryo quality and lower implantation rates, positing stress as a potential mediator in the physiological processes underlying successful IVF outcomes. 19,20…”
Section: The Analysis Underscores the Profound Influence Of Psycholog...mentioning
confidence: 99%